Volatile Markers of Chicken, Beef, and Pork Satay for Species Authentication - Indrasti, Dias; Mukhlisin, Muhammad Faqih; Darmawan, Noviyan; Yuliana, Nancy Dewi (Universitas Djuanda, 2025)
Satay is a popular dish in Indonesia. It is made from several pieces of meat skewered with bamboo sticks and then grilled over an open flame. Each type of satay meat has a distinct aroma due to its unique volatile component content. Volatilomics is a method that can be utilized to ensure the authenticity of meat products through the detection, characterization, and quantification of all easily vaporizing metabolites in a biological system. No research in Indonesia has previously applied volatilomics to differentiate meat species in satay. This study aimed to identify the volatile compound components in chicken, beef, pork, and mixed pork-containing satay, as well as determined the biomarker compounds for each type of satay meat by volatilomics approach. The volatile components in satay were extracted using the solid-phase microextraction (SPME) and analysed by gas chromatography-mass spectrometry (GC-MS). The data were processed using multivariate data analysis. Each type of satay meat exhibited good separation with the multivariate model. Beef and chicken satay were distinctly separated, whereas samples of pork and mixed pork-containing satay were positioned closely together. The hexadecanal, nonanoic acid, and ethylbenzene showed the strongest correlation in beef satay, whereas in chicken satay, the indicative compounds were benzaldehyde; 2,3,5-trimethyl-6-ethylpyrazine; and 2-nonenal, (E)-. The marker compounds for pork and mixed pork-containing satay were heptanal; 2-methylthiophene; and cyclooctene. The analysis using SPME-GC-MS successfully separated volatile compounds among the satay meats and determined the compounds contributing most strongly to the separation.